Non-Clinical Autistic Traits Correlate With Social and Ethical but Not With Financial and Recreational Risk-Taking - De Groot, Kristel (Frontiers in Psychology, 2020)
Previous research into uncertain and risky decision-making in Autism Spectrum Disorder (ASD) has been inconclusive, with some studies reporting less uncertain and risky decisions by persons with ASD compared to neurotypicals, but other studies failing to find such effects. A possible explanation for these inconsistent findings is that aberrant decision-making in ASD is domain-specific, and only manifests itself in domains related to autism symptomatology. The present study examines this premise by correlating self-reported autistic traits to individuals’ intention to engage in risky behaviours, their perception of how risky these behaviours are, and the amount of benefit they expect to obtain from engaging in them; all for five separate domains of decision-making: social, ethical, recreational, health/safety, and financial. In line with the hypotheses, persons with higher autistic traits reported reduced intention to engage in risky social behaviours and increased intention to engage in risky ethical behaviours. Furthermore, a positive correlation was found between autistic traits and risk perception in the social domain, indicating that persons with higher autistic traits perceive social behaviours as riskier than do persons with lower autistic traits. Correlations between autistic traits and individuals’ intention to engage in risky recreational and financial behaviours were small, and supported the null hypothesis (as shown by Bayes Factors). Given that most studies on uncertain and risky decision-making take place in a financial context, the present results could explain previous inconsistent findings on decision-making in ASD. Therefore, future studies should also examine decision-making outside the financial realm.